Human Capital and CEO Compensation during Institutional Transitions - Peng, Mike; Sun, S.; Markóczy, L. (Blackwell Publishing Ltd, 2015)
Firms appoint CEOs with different types of human capital in order to manage resource dependencies. How CEOs are compensated thus can be conceptualized as a valuation process of how boards view the value of CEOs' human capital. Two types of human capital - international experience and political ties - have emerged as potential drivers of CEO compensation during institutional transitions. But how they impact CEO compensation has remained unclear. We develop a resource dependence-based, contingency framework to focus on the external and internal factors that enable or constrain human capital to impact CEO compensation. Because of the tremendous regional diversity within China, externally, we focus on the level of marketization of the region in which firms are headquartered. Internally, we pay attention to two corporate governance mechanisms: politically connected outside directors and compensation committee. Data from 10,329 firm-year observations at 94 per cent of listed firms in China largely support our framework. Overall, our study contributes to resource dependence research by extending this research to the context of institutional transitions with a focus on how human capital impacts CEO compensation.